Analysis of Unfunction Fire Alarm Analysis on MT. Pangrango: Analisa Unfunction Fire Alarm System Pada MT. Pangrango - Brahmana, Dhea Haniel Gracella; Wiweko, Albert; Siregar, Muhammad Sapril (PT. Alpha Trianguli Australis, 2024)
Ships are a very efficient and effective means of transportation. With today's increasingly advanced, modern, and demanding developments, ships are also designed to be able to meet every expected human need. This research method uses a qualitative research approach which is analyzed descriptively. The research results show that an effective fire alarm system has enormous significance in the context of the maritime environment; maintenance of the detector will reduce the failure of the detector to detect fire so that the optical system and electronic circuit in the detector can work optimally. To ensure that the fire alarm is always operational in the event of a fire, we regularly test the alarm using our testing equipment.